ANALISIS PENGEMBANGAN E-MODUL SUBSTANSI MATERI GENETIKA BERBASIS LEARNING CYCLE 7E UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS SISWA - Patekur, Patekur (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2023)
The results of PISA in 2018 and TMSS in 2015 show that the quality of education in Indonesia in science and scientific problem solving is very low. The purpose of this study was to describe the analysis of the development of e-modules for the substance of genetic material integrated with YouTube based on Learning Cycle 7E to train critical thinking skills. This development research uses the ADDIE development model. This research is the initial stage of development, namely the analysis stage which includes analysis of needs, curriculum and materials. The subjects of this study were students of class XII MIPA 1 and XII MIPA 2 at SMAN 1 Paciran totaling 49 students, and 6 high school biology teachers in Lamongan Regency. Research data collection techniques with questionnaires and documentation. The questionnaire technique is based on the google form platform which is shared on WhatsApp groups. The research data were analyzed with quantitative descriptive statistics. The results of the study include needs analysis, 59.18% of teachers have difficulty in learning biology which trains students' critical thinking skills, and 81.63% of students have difficulty practicing critical thinking skills. The interest and need for e-modules resulted in 95.92% of teachers and 90.09% of students being interested and in dire need of developing e-modules based on Learning Cycle 7E. The results of the curriculum and material analysis are suitable for practicing critical thinking skills, because operational verbs are at the C4 and P4 levels in Bloom's taxonomy. This research can be concluded that teachers and students are interested and really need the development of e-modules based Learning Cycle 7E to train students' critical thinking.